Azimuthally invariant laser polarimetry of polycrystalline smears of biological liquids - Ushenko, Yu.O.; Dubolazov, O.V.; Motrich, A.V.; Bodnar, G.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The model based on Mueller-matrix description of mechanisms providing optical anisotropy typical for polycrystalline smears of liquor (including optical activity, birefringence as well as linear and circular dichroism) has been suggested. Within the statistical analysis of such distributions, the objective criteria of differentiation of smears of liquor taken from dead patient at different moments after his death have been determined. From the viewpoint of probative medicine, the operational characteristics (sensitivity, specificity and accuracy) of the method of Mueller-matrix reconstruction of optical anisotropy parameters have been found and the efficiency of this method in another task – diagnostics of diseases of internal organs of rats – has been demonstrated.